Seed Size Studies in relation to Yield Attributing Parameters in Indian Mustard [Brassica juncea (L) Czern and Coss] - A. KUMAR; R.P.S. TOMER; R. KUMAR; R.S. CHAUDHARY (Seed Research, 2026)
Studies on size grading in six cultivars of mustard for two years revealed that size grading significantly influences yield contributing characters. Among the six cultivars, RH-30 performed better for most of the yield characters viz. number of siliqua/plant, 1000-seed weight, seed yield/plant, length of main raceme and harvest index followed by the cv. Laxmi. A pronounced effed nounced effect of seed size was observed in large seed size category by having higher values of yield attributing parameters. Even the ungraded seed category was observed to be better for sowing purpose than small size of seed.